Rights and obligations of husband and wife when having sexual relations in the book of Fathul Izaar and Qurrotul 'Uyuun - Aminulloh, Izuddin Nur; Nisak, Khoirun; Budianto, Budianto (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
Sexual violence still occurs these days in the context of the household circumstances. Having viewed from the perspective of gender, Islamic law, as well as K.H Husein Muhammad's thoughts, it turns out that in sexual relations there are not only the husband's rights and the wife's obligations, but the wife also has rights and obligations that must be fulfilled by the husband. Fathul Izaar and Qurrotul 'Uyuun as books of sexology in Islamic boarding schools can actually lead to the achievement of rights & obligations for both husbands and wives in sexual relations. This research seeks to answer how the ethics of sexual relations in the book Fathul Izaar and Qurrotul 'Uyuun can lead to the fulfillment of rights & obligations when having sexual intercourse, both for husbands and wives. The research used a qualitative method, which was carried out using a library research approach. The primary sources in this study are the books of Fathul Izaar and Qurrotul 'Uyuun, while the secondary ones are documents that are compatible with the study that the researchers did. Data analysis in this study used qualitative content analysis techniques. The results indicate that: The ethics of sexual relations that researchers found in the books of Fathul Izaar and Qurrotul 'Uyuun can lead to the fulfillment of rights & obligations for both husbands and wives when having sexual intercourse, with the various ethics listed in the two books